2015
DOI: 10.1007/s12185-015-1810-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose acyclovir prophylaxis for the prevention of herpes simplex virus and varicella zoster virus diseases after autologous hematopoietic stem cell transplantation

Abstract: Limited data are available on prophylaxis for herpes simplex virus (HSV) and varicella zoster virus (VZV) disease following autologous hematopoietic stem cell transplantation (auto-HCT). We retrospectively reviewed the clinical charts of 105 consecutive patients who underwent their first auto-HCT at our institution between September 2007 and June 2014. Before August 2009, 30 patients received oral acyclovir at 1000 mg/day until engraftment, whereas after September 2009, 69 patients received oral acyclovir at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
(27 reference statements)
3
20
1
1
Order By: Relevance
“…Only one out of 12 patients (8·3%) without these risk factors experienced HZ following the addition of patients’ age (>56 years) to the risk factors in the present study. The incidence is equivalent to previous studies that used long‐term antiviral prophylaxis or vaccination (Kawamura et al , ; Winston et al , ). In contrast, one patient experienced HZ before engraftment in the clean room (7 days after auto‐HSCT), increasing the risk of outbreak.…”
Section: Univariate Analysis For Cumulative Incidence Of Herpes Zostersupporting
confidence: 62%
See 2 more Smart Citations
“…Only one out of 12 patients (8·3%) without these risk factors experienced HZ following the addition of patients’ age (>56 years) to the risk factors in the present study. The incidence is equivalent to previous studies that used long‐term antiviral prophylaxis or vaccination (Kawamura et al , ; Winston et al , ). In contrast, one patient experienced HZ before engraftment in the clean room (7 days after auto‐HSCT), increasing the risk of outbreak.…”
Section: Univariate Analysis For Cumulative Incidence Of Herpes Zostersupporting
confidence: 62%
“…The 1yCI of HZ after auto‐HSCT without antiviral prophylaxis was higher than that in previously reported cases receiving long‐term antiviral prophylaxis (Kawamura et al , ). Furthermore, the 1yCI of HZ in patients with a high number of chemotherapy cycles and a past history of HZ were high (40·6% and 100%, respectively).…”
Section: Univariate Analysis For Cumulative Incidence Of Herpes Zostercontrasting
confidence: 58%
See 1 more Smart Citation
“…Paradoxical finding of high effect size in low–dose acyclovir prophylaxis can be attributable to the large sample size of low–dose groups. A study by Kawamura et al suggested that low–dose acyclovir prophylaxis is effective to prevent VZV disease after HCT. Our results support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…VZV reactivation rate in the 6-month prophylaxis group was 17%, but did not reach statistical significance due to small numbers. Kawamura et al [24] retrospectively reviewed the clinical charts of 105 patients who underwent their first auto-HSCT between September 2007 and June 2014. Patients were divided into three groups according to the timing at which acyclovir prophylaxis was stopped after auto-HSCT: at engraftment, between engraftment and 1 year after auto-HSCT, and later than 1 year.…”
Section: Discussionmentioning
confidence: 99%